O3 / P2 mixed phase sodium-doped layered oxide material
By developing a sodium-doped layered oxide material with O3/P2 mixed phase, adjusting the relative proportion and controlling the preparation conditions, the problem of insufficient Na content of the cathode material of existing sodium ion battery is solved, and high electrochemical performance and long cycle life are achieved.
Patent Information
- Application Number
- CN202411827315.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-04-09
- Filing Date
- 2019-04-08
- Publication Date
- 2025-02-28
AI Technical Summary
The lack of Na content of existing sodium ion battery cathode materials leads to poor electrochemical performance, especially when charging at high voltages cannot maintain the charging capacity.
A sodium-doped layered oxide material with O3/P2 mixed phase was developed, and materials with excellent electrochemical properties were prepared by adjusting the relative proportion of the O3/P2 phase using specific reaction conditions.
It achieves high rate performance and discharge energy, extends the cycle life, and is suitable for use as an electrode active material.
Smart Images

Figure CN119528230A_ABST
Abstract
Description
[0001] This application is a divisional application of the PCT international application PCT / GB2019 / 051022 with a priority date of April 9, 2018, an application date of April 8, 2019, and an invention name of "O3 / P2 mixed phase sodium-doped layered oxide material", which entered the Chinese national stage on December 2, 2020 and has an application number of 201980037358.2. Field of the Invention
[0002] The present invention relates to novel O3 / P2 mixed phase sodium-doped layered oxide materials and methods for preparing the same. In addition, the present invention relates to the use of one or more of these novel O3 / P2 mixed phase sodium-doped layered oxide materials as electrode active materials, the electrode active materials being used in energy storage devices, such as batteries, in particular rechargeable batteries, alkali metal ion batteries, electrochemical devices and electrochromic devices; and to energy storage devices comprising one or more electrodes comprising one or more of the novel O3 / P2 mixed phase sodium-doped layered oxide materials. Background of the Invention
[0004] Sodium-ion batteries are similar in many ways to the lithium-ion batteries commonly used today; they are both reusable, secondary batteries that include an anode (negative electrode), a cathode (positive electrode), and electrolyte materials that are capable of storing energy, and both are charged and discharged through similar reaction mechanisms. + (or Li + ) ions are deintercalated from the cathode and intercalated into the anode. At the same time, electrons balancing the charge travel from the cathode through the external circuit containing the charger and into the anode of the battery. The same process occurs during discharge, but in the opposite direction.
[0005] Lithium-ion battery technology has received much attention in recent years and provides the preferred portable battery for most electronic devices in use today; however, lithium is not a cheap metal resource and is considered too expensive for use in large-scale applications. In contrast, sodium-ion battery technology is still in its infancy but is seen as having advantages; sodium is much more abundant than lithium, and some researchers predict that this will provide a cheaper and more durable way to store energy in the future, especially for large-scale applications such as storing energy on the grid. However, much work needs to be done before sodium-ion batteries become a commercial reality.
[0006] It is known that the general formula A xMetal oxides of MO2 (where A represents one or more alkali metal ions and M represents one or more metal ions, at least one of which has several oxidation states, such as transition metals) crystallize in a variety of different layered structures. C. Delmas et al. describe this in detail in "Structural Classification and Properties of the Layered Oxides", Physica 99B (1980) 81-85. In summary, these structures are all formed by (MO2) n The sheets of MO6 are made up of octahedral edges. These sheets are stacked one on top of the other and are separated by alkali metal atoms, and the exact position of the alkali metal will determine whether the overall structure of the metal oxide is described as octahedral (O), tetrahedral (T) or prismatic (P). In a lattice composed of hexagonal sheets, there are three possible positions for oxygen atoms, usually called A, B and C. It is the order in which these sheets are stacked together that creates the O, T and P environments. The number 2 or 3 is also used to describe the number of alkali metal layers in the repeating unit perpendicular to the layering. For example, when the layers are stacked in the order ABCABC, the O3 structure is obtained. This is interpreted as there are 3 alkali metal layers in the repeating unit, and each alkali metal is in an octahedral environment. This material is characterized by the alkali metal ions being octahedral oriented, and a typical compound with this structure is A x MO2 (x ≤ 1). The order ABAB of alkali metal ions with tetrahedral orientation will produce the T1 structure, which is represented by the A2MO2 compound. Stacking the sheets in the ABBA order gives the P2 structure, in which half of the prisms share edges with the MO6 octahedron and the other half share faces. A typical compound is A ≈0.7 MO2. Finally, stacking in the ABBCCA sequence produces the P3 structure type, in which all prisms share one face with a MO6 octahedron and three edges with three MO6 octahedra in the next layer. ≈0.5 The MO2 compound adopts the P3 structure. It will be noted that the work of Delmas showed that A x The amount of alkali metal present in the MO2 material is directly related to the overall structure of the metal oxide.
[0007] YJ Shin et al. further studied A x MO2 compounds, in Solid State Ionics 132 (2000) 131-141 reported layered oxides Na where x is in the range of 0.6 ≤ x ≤ 1.0 x Ni x / 2 Ti 1-x / 2Preparation and structural properties of O2. In particular, the paper discloses that a single phase of rhombohedron (O type) is observed when 0.72 < x ≤ 1.0, while a single phase of hexagonal lattice (P type) is observed when 0.6 ≤ x ≤ 0.72. The paper also points out that although a mixture of both O and P structure types is generated when 0.6 ≤ x ≤ 0.72 is heated at about 1223 K (about 950°C), a single phase of P structure type is generated when the mixture is heated above about 1373 K (about 1100°C).
[0008] Other researchers, such as M. Pollet et al., entitled "Structure and Properties of Alkali Cobalt Double Oxides A 0.6 CoO2 (A=Li, Na and K) J. Inorg. Chem. 2009,48, 9671-9683 reported that when A is lithium, the compound crystallizes in the O3 structure; when A is sodium, it adopts the P'3 structure; when A is potassium, it is the P2 system. Meanwhile, G. Ceder et al. described further insights into the relationship that seems to exist between sodium content and lattice parameters in "Synthesis and Stoichiometry of Different Layered Sodium Cobalt Oxides" Chem. Mater. 2014, 26, 5288-5796. They concluded that when Na x When CoO2 is heated to 450 to 750 °C and x is 0.60 to 1.05, single phase domains O3, O'3 and P'3 can be obtained only when x is clearly 1.00, 0.83, 0.67, respectively, and a single P2 phase will be obtained when x is in the range of 0.68 to 0.76.
[0009] Finally, the document by Shaohua Guo et al.: "A layered P2- and O3-type composite as a high-energy cathode for rechargeable sodium-ion batteries (Angewandte Chemie 54, 5894-5899, 2015) describes a compound having the following general formula: Na 0.66 Li 0.18 Mn 0.71 Ni 0.21 Co 0.08 O 2-δ, which is calculated using the δ values commonly known in the art (i.e. in the range of 0 to 0.1) as a compound comprising a manganese ion in an oxidation state less than 4+. Such a compound is completely different from the material of the present invention and its behavior is completely different from the material of the present invention electrochemically.
[0010] The requirements for rechargeable batteries in terms of cost, capacity, weight, voltage and battery volume will depend on their end-use application requirements. For example, household and commercial load-leveling applications will require compact battery packs with high volumetric energy density, while portable electronic devices require lightweight and small battery packs, i.e. high weight and volumetric energy density; other applications may require high power, for which the battery must achieve high operating voltages and show high ionic and electronic conductivity.
[0011] It is well known that layered sodium-ion battery cathode materials (such as sodium transition metal oxides (Na x MO2 compounds) are usually Na deficient (x = 0.6 to 0.72) and are P2 phase materials. For example, Lu and Dahn, J. Electrochem. Soc., 2001, 148, A710-715 demonstrated that P2 layered oxides Na 2 / 3 [Ni 1 / 3Mn 2 / 3 ]O2 can reversibly exchange Na ions in the sodium half-cell. In addition, Shirley Meng and DH Lee, Phys.Chem. Chem. Phys., 2013, 15, 3304 reported P2-Na 2 / 3 [Ni 1 / 3 Mn 2 / 3 ]O2 shows excellent cycling and high-rate performance, but it should be noted that these results are only achieved when the material is charged below 4.22 V; above 4.22 V, the charge capacity cannot be maintained during cycling due to the phase transformation from P2 to O2.
[0012] In contrast, sodium transition metal oxides (Na x MO2 compounds) typically contain more sodium (x = 0.72 to 1.00), and structural analysis suggests that they are O3 phase materials.
[0013] As described in “Review – Manganese-Based P2-Type Transition Metal Oxides as Sodium-ion Battery Cathode Materials” by RJ Clement et al., J. Electrochem Soc., 162 (14) A2589-A2604 (2015), several research groups have studied composite layered transition metal oxide cathode materials, and recent work has shown that lithium incorporation into NaNi 0.5 Mn 0.5 O2 leads to the topological symbiosis of P2 and O3 domains in the structure and produces materials with improved specific capacity and rate performance. The high capacity is achieved because the O3 phase provides a larger sodium ion storage space; the Na +The ions diffuse easily during the charge and discharge operation, thus achieving high rate performance. Patent application PCT / GB2015 / 051482 relates to a mixture of doped nickelate components, comprising: one or more components of a first component type having an O3 phase structure, wherein the amount of alkali metal is 0.85 to 1 and the amount of nickel is <0.5; and one or more additional component types, which are selected from one or more of one or more components of a second component type having a P2 phase structure, wherein the amount of alkali metal is 0.4 to <1 and the amount of nickel is <0.5; and one or more components of a third component type having a P3 phase structure, wherein the amount of alkali metal is 0.4 to <1 and the amount of nickel is <0.5. It should be noted that the O3, P2 and P3 structures of each of the first, second and third component types appear to be determined by the amount of alkali metal they each contain. Mixed phase compositions are described as being prepared by mixing ready-made O3 phase materials with ready-made P2 phase materials and / or P3 phase materials, or by heating a mixture of precursor materials of O3, P2 and / or P3 materials. In the latter case in particular, the resulting mixed phase composition is disclosed in the form of a "weight average" molecular formula, and this is interpreted as being determined by the relative proportions of the starting materials, and is definitely not determined by any direct measurement or composition analysis of the resulting mixed phase composition itself. Some specific examples in this prior art are first described by their weight average molecular formula, and secondly by the XRD patterns provided, indicating that the resulting mixed phase composition comprises a mixture of two or more phase types. However, not only is there no disclosure in this prior art about the actual ratio achieved for these two or more phase types, but the prior art explicitly teaches that, whatever the ratio is, it depends on which is the most thermodynamically preferred mixture of the compositions of the O3, P2 and P3 phases, and this will be based on the relative proportions of the starting materials. As described above, in order to prepare an O3 phase type material, the starting material must contain 0.85 to 1 part of an alkali metal, and in order to prepare a P2 phase type material, the starting material must contain 0.4 to less than 1 part of an alkali metal.
[0014] Contrary to the teachings in the prior art as described above, current workers have found that changing the amount of alkali metal in the layered oxide material is not the only way to control the phase structure of the material, i.e., not the only way to control whether the material adopts an O3 or P2 phase structure. In addition, they surprisingly found that when any specific sodium-doped layered oxide material is prepared from a mixture of precursor materials selected to provide a stoichiometric ratio of metal atoms present in a specific sodium-doped layered oxide material (within the range of possible chemical formulas), depending on the exact method used, a sodium-doped layered oxide material having a single O3 phase structure, or a single P2 phase structure or a mixture of O3 and P2 phase structures can be prepared; the latter may be rich in P2 or rich in O3 or P2 and O3 are equal. Even more surprisingly, the inventors have found that in the case of a mixture of phases coexisting, a specific ratio of O3 to P2 phases will have a significant effect on the electrochemical properties exhibited by the sodium-doped layered oxide material. Therefore, the specific reaction conditions (rather than the amount of alkali metal present) can be selected to adjust the relative ratio of the O3 / P2 phases, which in turn can produce active materials with excellent specific rate performance and discharge energy as well as increased cycle life.
[0015] Therefore, the present invention provides significant improvements in the following aspects: i) providing a series of new O3 / P2 mixed phase sodium-doped layered oxide materials; ii) providing a series of new O3 / P2 mixed phase sodium-doped layered oxide materials, which provide electrochemical properties that are superior to those of other known sodium-doped layered oxide materials, making them particularly suitable for use as electrode active materials, which are used in electrodes, especially cathodes, energy storage devices, such as batteries, especially rechargeable batteries, sodium ion batteries, electrochemical devices and electrochromic devices; and iii) providing new, simple and cost-effective methods to control and thus customize the O3 / P2 phase ratio in sodium-doped layered oxide materials to prepare materials with specific electrochemical properties.
[0016] Therefore, the present invention provides an O3 / P2 mixed phase sodium-doped layered oxide material, which comprises a mixture of phases, wherein the first phase has an O3 type structure and the second phase has a P2 type structure; in addition, wherein the mixed phase sodium-doped layered oxide material has the general formula:
[0017] Na a A b M 1 c M 2 d M 3 e M 4 f M 5 gO 2±δ ;
[0018] in:
[0019] A is at least one alkali metal selected from lithium and potassium;
[0020] M 1 is one or more metals having an average oxidation state of 2+;
[0021] M 2 is one or more metals with an average oxidation state of 4+;
[0022] M 3 is one or more metals with an average oxidation state of 2+;
[0023] M 4 is one or more metals having an average oxidation state of 4+; and
[0024] M 5 One or more metals with an average oxidation state of 3+
[0025] in:
[0026] a>0;
[0027] a>b, preferably b=0;
[0028] 0.75 ≤ (a+b) ≤ 1.0; preferably 0.75 ≤ (a+b) < 0.95; further preferably 0.77 ≤ (a+b) ≤ 1.0, particularly preferably 0.79 ≤ (a+b) < 0.93, and ideally 0.80 ≤ (a+b) < 0.94;
[0029] 0 ≤ c < 0.5, preferably 0 < c ≤ 0.48, further preferably 0.25 ≤ c ≤ 0.46, and ideally 0.28 ≤ c ≤ 0.46;
[0030] At least one of d and f > 0;
[0031] e > 0;
[0032] 0 ≤ g < 0.5;
[0033] 0 ≤ δ ≤ 0.1; preferably δ=0;
[0034] Where: a, b, c, d, e, f, and g are chosen to maintain electrical neutrality;
[0035] wherein the O3 / P2 mixed phase sodium-doped layered oxide material comprises >0 to <100% of the first phase having an O3 type structure, and <100 to >0% of the second phase having a P2 type structure, based on the combined total moles of the first phase and the second phase present in the mixed phase sodium-doped layered oxide material;
[0036] And wherein the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention does not include a layered oxide having the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 material, the material comprising a mixture of a first phase having an O3 type structure and a second phase having a P2 type structure, wherein the Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 The total molar amount of the first phase and the second phase present in the O2 material, the first phase being 63% and the second phase being 37%;
[0037] and does not include the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 material, the material comprising a mixture of a first phase having an O3 type structure and a second phase having a P2 type structure, wherein the Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 The total molar number of the first phase and the second phase present in the O2 material is 97% of the first phase and 3% of the second phase.
[0038] For the avoidance of doubt, the present invention includes the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 material, the material comprising an amount other than 63% of a first phase having an O3 type structure, and an amount other than 37% of a second phase having a P2 type structure; and further comprising a formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 material, the material containing an amount other than 97% of a first phase having an O3 type structure and an amount other than 3% of a second phase having a P2 type structure.
[0039] Preferably, based on the total molar number of the O3 type phase and the P2 type phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the amount of the P2 type phase contained in the O3 / P2 mixed phase sodium-doped layered oxide material according to the present invention is in one or more ranges selected from the following: >0%, >5%, >10%, >15%, >20%, >25%, >30%, >35%, >40%, >45%, >50%, >55%, >60%, >65%, >70%, >75%, >80%, >85%, >90%, >95% and <100% (when the O3 / P2 mixed phase sodium-doped layered oxide material has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 When O2 is not 37% and when the O3 / P2 mixed phase contains sodium doped layered oxide material having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 Alternatively, or in addition, in any combination of one or more of the percentages of the amount of the P2-type phase present in the aforementioned O3 / P2 mixed phase sodium-doped layered oxide material, based on the total molar number of the O3-type phase and the P2-type phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the amount of the P2-type phase present is within one or more of the following ranges: <100%, <95%, <90%, <85%, <80%, <75%, <70%, <65%, <60%, <55%, <50%, <45%, <40%, <35%, <30%, <25%, <20%, <15%, <10%, <5%, >0% (when the O3 / P2 mixed phase sodium-doped layered oxide material has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 When O2 is not 37% and when the O3 / P2 mixed phase contains sodium doped layered oxide material having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 Since the amount of O3 phase plus the amount of P2 phase are normalized to equal 100%, the amount of O3 phase present can be unambiguously inferred from the amount of P2 phase (as described below).
[0040] Further preferably, based on the total molar number of the O3 type phase and the P2 type phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the O3 / P2 mixed phase sodium-doped layered oxide material according to the present invention comprises 51% to 99%, but not 63% or 97%; preferably 51% to <63% and >63% to <97, and >97 to 99%; further preferably 51 to 62% and 64% to 96% and 98% to 99% of the first phase having an O3 type structure (when the O3 / P2 mixed phase sodium-doped layered oxide material has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2), and 1 to 49%, but not 3% or 37%; preferably 1 to <3% and >3% to <37% and >37 to 49%; further preferably 1% to 2% and 4% to 36% and 38% to 49% of a second phase having a P2 type structure (when the O3 / P2 mixed phase sodium-doped layered oxide material has the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2).
[0041] Preferably M 1 is one or more metals in the oxidation state 2+;
[0042] M 2 is one or more metals in the oxidation state 4+;
[0043] M 3 is one or more metals in the oxidation state 2+;
[0044] M 4 is one or more metals in the oxidation state 4+; and
[0045] M 5 It is one or more metals in the oxidation state 3+.
[0046] In the preferred O3 / P2 mixed phase sodium-doped layered oxide material according to the present invention, M 1 comprising or consisting of one or more metals in oxidation state 2+ selected from nickel, iron, manganese, cobalt, copper, magnesium, calcium and zinc; M 2 Comprising or consisting of one or more metals in oxidation state 4+ selected from manganese, titanium and zirconium; M 3 comprising or consisting of one or more metals in oxidation state 2+ selected from magnesium, calcium, copper, zinc and cobalt; M 4 comprising or consisting of one or more metals in oxidation state 4+ selected from manganese, titanium and zirconium; and M 5It comprises or consists of one or more metals in the oxidation state 3+ selected from aluminum, iron, cobalt, molybdenum, chromium, vanadium, scandium and yttrium. It is particularly preferred that M 1 Comprising or consisting of nickel in the oxidation state 2+.
[0047] Metal M 2 and M 4 It can be the same or different metals in oxidation state 4+. 2 and M 4 can be interchanged with each other. 2 = M 4 When, the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention can be written as:
[0048] Na a A b M 1 c M 2 d M 3 e M 4 f M 5 g O 2±δ ,
[0049] or
[0050] Na a A b M 1 c M 2 d+f M 3 e M 5 g O 2±δ ,
[0051] or
[0052] Na a A b M 1 c M 3 e M 4 f+d M 5 g O 2±δ ,
[0053] And all these forms of the stated formula are considered equivalent.
[0054] When b=0, the O3 / P2 mixed phase sodium-doped layered oxide material does not contain any lithium or potassium, that is, the material contains sodium as the only alkali metal.
[0055] When a > b, the O3 / P2 mixed phase sodium-doped layered oxide material comprises i) sodium alone, or ii) a mixture of sodium and one or more additional alkali metals selected from lithium and potassium, wherein the amount of sodium is greater than the amount of the additional alkali metals, or, if more than one additional alkali metal is present, the amount of sodium is greater than the combined amount of the more than one additional alkali metals.
[0056] The percentage values of the first phase and the second phase mentioned herein are calculated as a percentage of the total molar number of the first phase having an O3 type structure plus the second phase having a P2 type structure present in the O3 / P2 mixed phase sodium-doped layered oxide material. This calculation is based only on the amount of P2 phase material and the amount of O3 phase material present in the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention. That is, it is assumed that O3 + P2 is normalized to 100%, and the presence and amount of any impurities are ignored for the purpose of this calculation.
[0057] As referred to herein, an impurity is defined as any material that does not have an O3 or P2 type phase structure, for example, nickel oxide (NiO) is a common impurity that may be formed when preparing doped layered oxide materials when using solid-state reaction methods.
[0058] The terms "O3-type phase" and "O3 phase" mentioned herein should be considered equivalent to each other and can be used interchangeably. Similarly, the P2-type phase and P2 phase mentioned herein should also be considered equivalent to each other and can be used interchangeably. In addition, the term "O3 phase" or "O3-type phase" will include one or more similar O3 phases, such as secondary O3 phases and distorted O3 phases, the latter of which are generally referred to as O3' phases by those skilled in the art, and the term "P2 phase" or "P2-type phase" will include one or more similar P2 phases, such as secondary P2 phases and distorted P2 phases, the latter of which are generally referred to as P2' phases. Two or more O3 (or P2)-type phases can coexist, and these phases usually appear due to specific target compositions and methods used to prepare them.
[0059] Ideally, quantitative phase analysis is performed to determine the molar ratio of the O3 / P2 phase in the O3 / P2 mixed phase sodium-doped layered oxide material according to the present invention by performing a technique known in the art as "Rietveld refinement analysis" on the structural parameters from the X-ray diffraction data. The "Whole Pattern Fitting Structure Refinement" invented by Hugo Rietveld is now widely recognized as a very valuable method for structural analysis of almost all types of crystalline materials, and is particularly useful for determining the composition of materials containing a mixture of crystalline phases. It is a software method that obtains a calculated diffraction pattern by refining various indicators, including lattice parameters, peak width and shape, and preferred orientation. The diffraction pattern is then refined until it is as close as possible to the unknown composition to be tested. Various properties related to the test composition can be obtained, including: accurate quantitative information, grain size, and site occupancy factor. Compared with conventional quantitative methods, the advantage of Rietveld analysis is that no standard materials are required, and it is possible to achieve accurate results within ±1%.
[0060] Preferably, the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention comprises M 1 , which includes one or more metals with an oxidation state of 2+, the metal being selected from nickel, iron, manganese, cobalt, copper, magnesium, calcium and zinc. Particularly preferably, the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention comprises M 1 , which comprises or consists of one or more metals in oxidation state 2+, the metals being selected from nickel, iron, cobalt and calcium. Particularly preferred is the O3 / P2 mixed phase sodium-doped layered nickelate material.
[0061] Further preferably, the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention is selected from:
[0062] NeNi 0.400 Mn 0.490 Mg 0.100 Ti 0.010 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0063] Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 (comprising 1% to 99%, but not 97%, of a first phase having an O3-type structure, and 99% to 1%, but not 3%, of a second phase having a P2-type structure);
[0064] Na 0.925 Ni 0.4525 Mn 0.5275 Mg 0.01 Ti 0.01 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0065] Na 0.867 Ni 0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0066] Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 O2 (comprising 1% to 99%, but not 63%, of a first phase having an O3-type structure, and 99% to 1%, but not 37%, of a second phase having a P2-type structure);
[0067] Na 0.8 Ni 0.35 Mn 0.48 Mg 0.05 Ti 0.12 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0068] Na 0.77 Ni 0.28 Mn 0.31 Mg 0.05 Ti 0.25 Fe 0.11 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0069] Na 0.77 Ni 0.225 Mn 0.115 Mg 0.01 Ti 0.35 Fe 0.3 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0070] Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0071] Na 0.833 Ni 0.317 Mn 0.417 Mg 0.05 Ti 0.117 Co 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0072] Na 0.867 Ni 0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0073] Na 0.85 Ni 0.325 Mn 0.525 Mg 0.100 Ti 0.05 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0074] Na 0.85 Ni 0.325 Mn 0.499 Mg 0.100 Ti 0.076 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0075] Na 0.77 Ni 0.305 Mn 0.51 Mg 0.025 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0076] Na 0.77 Ni 0.305 Mn 0.535 Mg 0.025 Ti 0.025 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0077] NeNi 0.4 Mn 0.49 Mg 0.1 Ti 0.01 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0078] Na 0.77 Ni 0.28 Mn 0.51 Mg 0.05 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0079] Na 0.833 Fe 0.200 Mn 0.483 Mg 0.0917 Cu 0.225 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0080] NaLi 0.05 Ni 0.3 Mn 0.525 Mg 0.025 Cu 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0081] Na 0.775 Ni 0.35 Mn 0.475 Ti 0.1 Al 0.075 O2 (comprising 1% to 99% of a first phase having an O3 type structure and 99% to 1% of a second phase having a P2 type structure); and
[0082] Na 0.833 Ca 0.05 Ni 0.3417 Mn 0.4417 Mg 0.125 Ti 0.0917 O2 (comprising 1% to 99% of a first phase having an O3 type structure and 99% to 1% of a second phase having a P2 type structure).
[0083] As described above, the percentage value of each of the first phase and the second phase is based on the combined total molar number of the first phase having an O3 type structure and the second phase having a P2 type structure present in the O3 / P2 mixed phase sodium-doped layered oxide material.
[0084] Preferably, the present invention provides an O3-rich O3 / P2 mixed phase sodium-doped layered oxide material having the above general structure, wherein the material comprises a mixture of phases in which a first phase has an O3-type structure and a second phase has a P2-type structure, wherein the amount of the first phase is 51 to 99% based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material (but when the O3 / P2 mixed phase sodium-doped layered oxide material has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 does not include 63%, or when the O3 / P2 mixed phase contains sodium doped layered oxide material having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 does not include 97%), and the content of the second phase is 1 to 49% (but when the O3 / P2 mixed phase contains sodium doped layered oxide material having the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 does not include 37%, or when the O3 / P2 mixed phase contains sodium doped layered oxide material having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 Alternatively, preferably, the present invention provides a P2-rich O3 / P2 mixed phase sodium-doped layered oxide material having the above general structure, the material comprising a mixture of phases in which a first phase has an O3 type structure and a second phase has a P2 type structure, wherein the amount of the first phase is 1 to 49%, and the amount of the second phase is 51 to 99%, based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material.
[0085] Contrary to the disclosures in the prior art that teach mixed-phase sodium-doped layered oxide materials having an average composition calculated from the ratio of the starting raw materials, the applicant unexpectedly discovered that a series of different O3 / P2 phase ratios can be produced for each sodium-doped layered oxide material, which is independent of the composition of the material (e.g., the amount of alkali metal and / or nickel present). Further unexpectedly, the applicant has discovered that by changing the process conditions for preparing the target sodium-doped layered oxide material, in particular by changing the heating temperature and / or heating duration, a series of different O3 / P2 phase ratios can be obtained for a single target sodium-doped layered oxide material composition. As a general principle, the applicant has discovered that when the heating temperature (reaction temperature) of the reaction process is gradually increased from 500°C, in any specific target sodium-doped layered oxide material, the proportion of the phase having the O3 structure increases relative to the proportion of the phase having the P2 structure. They also found that, in addition or alternatively, in any specific target sodium-doped layered oxide material, increasing the reaction time also increases the proportion of the phase having the O3 structure relative to the proportion of the phase having the P2 structure. As defined herein, the reaction time is the duration for which the reaction mixture is heated at the desired reaction temperature. Specific examples demonstrating these phenomena are provided below.
[0086] The chemical formula of each of the O3 / P2 mixed phase sodium-doped layered oxide materials according to the present invention will fall within the above general formula, and each of these O3 / P2 mixed phase sodium-doped layered oxide materials can be conveniently synthesized by reacting precursor materials together in amounts required to provide the stoichiometric ratio of the metal atoms present in the specific O3 / P2 mixed phase sodium-doped layered oxide material to be synthesized (the latter is also referred to herein as the "target" O3 / P2 mixed phase sodium-doped layered oxide material). The target O3 / P2 mixed phase sodium-doped layered oxide material will contain a mixture of phases, wherein the first phase will have an O3 type structure and the second phase will have a P2 type structure, wherein the target O3 / P2 mixed phase sodium-doped layered oxide contains 1 to 99% of the first phase based on the total molar number of the first phase and the second phase present in the target O3 / P2 mixed phase sodium-doped layered oxide material (but when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 63%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxide having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083O2) and 99 to 1% of a second phase (but when the target O3 / P2 mixed phase contains a sodium-doped layered oxide having the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 37%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxides having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 is not 3%).
[0087] Therefore, the present invention also provides a method for preparing the O3 / P2 mixed phase sodium-doped layered oxide material as described above, which has the general formula:
[0088] Na a A b M 1 c M 2 d M 3 e M 4 f M 5 g O 2±δ ;
[0089] in:
[0090] A is at least one alkali metal selected from lithium and potassium;
[0091] M 1 is one or more metals having an average oxidation state of 2+;
[0092] M 2 is one or more metals having an average oxidation state of 4+;
[0093] M 3 is one or more metals having an average oxidation state of 2+;
[0094] M 4 is one or more metals having an average oxidation state of 4+; and
[0095] M 5 One or more metals with an average oxidation state of 3+
[0096] in:
[0097] a>0;
[0098] a>b, preferably b=0;
[0099] 0.75 ≤ (a+b) ≤ 1.0; preferably 0.75 ≤ (a+b) < 0.95; further preferably 0.77 ≤ (a+b) ≤ 1.0, particularly preferably 0.79 ≤ (a+b) < 0.93, and ideally 0.80 ≤ (a+b) < 0.94;
[0100] 0 ≤ c < 0.5, preferably 0 < c ≤ 0.48, further preferably 0.25 ≤ c ≤ 0.46, and ideally 0.28 ≤ c ≤ 0.46;
[0101] At least one of d and f > 0;
[0102] e > 0;
[0103] 0 ≤ g < 0.5;
[0104] 0 ≤ δ ≤ 0.1; preferably δ=0;
[0105] Where: a, b, c, d, e, f, and g are chosen to maintain electrical neutrality;
[0106] wherein the O3 / P2 mixed phase sodium-doped layered oxide material comprises a mixture of phases in which a first phase has an O3 type structure and a second phase has a P2 type structure;
[0107] Wherein, based on the total molar number of the first phase and the second phase present in the target O3 / P2 mixed phase sodium-doped layered oxide material, the amount of the first phase is 1 to 99%, and the amount of the second phase is 99 to 1%, and the method comprises the following steps:
[0108] i) forming a mixture of precursor materials to provide a stoichiometric ratio of metal atoms present in the target O3 / P2 mixed phase sodium-containing doped layered oxide material; and
[0109] ii) heating the resulting mixture at a temperature of at least 500° C. to produce the target O3 / P2 mixed phase sodium-doped layered oxide material;
[0110] and wherein the method does not involve any of the following:
[0111] i) Formation provides a presence of Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 A mixture of precursor materials of an O3 / P2 mixed phase containing sodium doped layered oxide materials in a stoichiometric ratio of metal atoms, and
[0112] ii) heating the resulting mixture at 900° C. for 10 hours to produce an O3 / P2 mixed phase sodium-doped layered oxide material comprising a mixture of phases in which a first phase has an O3 type structure and a second phase has a P2 type structure,
[0113] wherein based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the amount of the first phase is 63%, and the amount of the second phase is 37%;
[0114] or
[0115] i) Formation provides a presence of Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 A mixture of precursor materials of an O3 / P2 mixed phase containing sodium doped layered oxide materials in a stoichiometric ratio of metal atoms, and
[0116] ii) heating the resulting mixture at 900° C. for 4 minutes to produce an O3 / P2 mixed phase sodium-doped layered oxide material comprising a mixture of phases in which a first phase has an O3 type structure and a second phase has a P2 type structure,
[0117] Wherein, based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the amount of the first phase is 97%, and the amount of the second phase is 3%.
[0118] As mentioned above, preferably, M 1 is one or more metals in the oxidation state 2+;
[0119] M 2 is one or more metals in the oxidation state 4+;
[0120] M 3 is one or more metals in the oxidation state 2+;
[0121] M 4 is one or more metals in the oxidation state 4+; and
[0122] M 5 It is one or more metals in the oxidation state 3+.
[0123] The present invention advantageously provides a method for preparing the target O3 / P2 mixed phase sodium-doped layered oxide material as described above, wherein the material comprises 51% to 99% of a first phase having an O3-type structure (but when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 63%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxide having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 is not 97%); preferably 51% to <63% and >63% to <97% and >97 to 99%; further preferably 51 to 62% and 64% to 96% and 98% to 99%; and 1 to 49% of a second phase having a P2-type structure (but when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 37%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxides having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 is not 3%); preferably 1 to <3% and >3% to <37% and >37 to 49%; further preferably 1% to 2% and 4% to 36% and 38% to 49%;
[0124] The method comprises the following steps:
[0125] i) forming a mixture of precursor materials to provide a stoichiometric ratio of metal atoms present in the target O3 / P2 mixed phase sodium-containing doped layered oxide material; and
[0126] ii) heating the resulting mixture to a temperature of at least 500° C. to produce the target O3 / P2 mixed phase sodium-doped layered oxide material.
[0127] The present invention provides another method for preparing the O3 / P2 mixed phase sodium-doped layered oxide material as described above and having the following general formula:
[0128] Na a A b M1 c M 2 d M 3 e M 4 f M 5 g O 2±δ ;
[0129] in:
[0130] A is at least one alkali metal selected from lithium and potassium;
[0131] M 1 is one or more metals with an average oxidation state of 2+;
[0132] M 2 is one or more metals with an average oxidation state of 4+;
[0133] M 3 is one or more metals with an average oxidation state of 2+;
[0134] M 4 is one or more metals having an average oxidation state of 4+; and
[0135] M 5 One or more metals with an average oxidation state of 3+
[0136] in:
[0137] a>0;
[0138] a>b, preferably b=0;
[0139] 0.75 ≤ (a+b) ≤ 1.0; preferably 0.75 ≤ (a+b) < 0.95; further preferably 0.77 ≤ (a+b) ≤ 1.0, particularly preferably 0.79 ≤ (a+b) < 0.93, and ideally 0.80 ≤ (a+b) < 0.94;
[0140] 0 ≤ c < 0.5, preferably 0 < c ≤ 0.48, further preferably 0.25 ≤ c ≤ 0.46, and ideally 0.28 ≤ c ≤ 0.46;
[0141] At least one of d and f > 0;
[0142] e > 0;
[0143] 0 ≤ g < 0.5;
[0144] 0 ≤ δ ≤ 0.1; preferably δ=0;
[0145] Where: a, b, c, d, e, f, and g are chosen to maintain electrical neutrality;
[0146] And wherein the O3 / P2 mixed phase sodium-doped layered oxide material comprises 1 to 99% of the first phase having an O3 type phase structure and 99 to 1% of the second phase having a P2 type phase structure based on the total molar number of the first phase and the second phase present in the target O3 / P2 mixed phase sodium-containing material, the method comprises the following steps:
[0147] i) forming a mixture of precursor materials to provide a stoichiometric ratio of metal atoms present in the target O3 / P2 mixed phase sodium-containing doped layered oxide material; and
[0148] ii) heating the resulting mixture at a temperature of at least 500° C. for a period of time ranging from greater than 4 minutes to less than 10 hours to produce the target O3 / P2 mixed phase sodium-doped layered oxide material.
[0149] The above method of the present invention produces a target material as defined above, wherein M 1 comprising or consisting of one or more metals in oxidation state 2+ selected from nickel, iron, manganese, cobalt, copper, magnesium, calcium and zinc; M 2 Comprising or consisting of one or more metals in oxidation state 4+ selected from manganese, titanium and zirconium; M 3 comprising or consisting of one or more metals in oxidation state 2+ selected from magnesium, calcium, copper, zinc and cobalt; M 4 comprising or consisting of one or more metals in oxidation state 4+ selected from manganese, titanium and zirconium; and M 5 The present invention is characterized in that the target O3 / P2 mixed phase sodium-doped layered oxide material comprises one or more metals in the oxidation state 3+ selected from aluminum, iron, cobalt, molybdenum, chromium, vanadium, scandium and yttrium or consists thereof. 1 , which comprises one or more metals in the oxidation state 2+ selected from nickel, iron, manganese, cobalt, copper, magnesium, calcium and zinc. It is particularly preferred that the target O3 / P2 mixed phase sodium-doped layered oxide material comprises M 1 , which comprises one or more metals selected from nickel, iron, cobalt and calcium in oxidation state 2+. The target O3 / P2 mixed phase sodium-doped layered nickelate material is particularly preferred.
[0150] Ideally, the method of the present invention provides an O3 / P2 mixed phase sodium-doped layered oxide material having the above general structure, comprising 51 to 99% of the first phase having an O3-type structure (but when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 63%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxide having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2), and 1 to 49% of a second phase having a P2-type structure (but not when the target O3 / P2 mixed phase contains a sodium-doped layered oxide having the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 37%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxides having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 is not 3%).
[0151] Preferably, the method of the present invention provides an O3-rich O3 / P2 mixed phase sodium-doped layered oxide material having the above general structure, wherein the material comprises a mixture of phases in which a first phase has an O3-type structure and a second phase has a P2-type structure, wherein the amount of the first phase is 51 to 99% based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material (but when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 63%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxide having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 is not 97%), and the amount of the second phase is 1 to 49% (but when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 37%, or when the target O3 / P2 mixed phase contains sodium-doped layered oxides having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 is not 3%).
[0152] Alternatively, preferably, the method of the present invention provides a P2-rich O3 / P2 mixed phase sodium-doped layered oxide material having the above-mentioned general structure, wherein the material comprises a mixture of phases in which a first phase has an O3 type structure and a second phase has a P2 type structure, wherein based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the amount of the first phase is 1 to 49%, and the amount of the second phase is 51 to 99%.
[0153] Further preferably, the method of the present invention provides an O3 / P2 mixed phase sodium-doped layered oxide material as described above, wherein the amount of the P2-type phase based on the total molar number of the O3-type phase and the P2-type phase present in the O3 / P2 mixed phase sodium-doped layered oxide material is in one or more ranges selected from the group consisting of: >0%, >5%, >10%, >15%, >20%, >25%, >30%, >35%, >40%, >45%, >50%, >55%, >60%, >65%, >70%, >75%, >80%, >85%, >90%, >95% and <100% (when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 37% or when the target O3 / P2 mixed phase contains sodium-doped layered oxides having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083In addition or alternatively, and in any combination with the percentage of the amount of the P2-type phase present in the aforementioned O3 / P2 mixed phase sodium-doped layered oxide material, based on the total molar number of the O3-type phase and the P2-type phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the amount of the P2-type phase present is within one or more of the following ranges: <100%, <95%, <90%, <85%, <80%, <75%, <70%, <65%, <60%, <55%, <50%, <45%, <40%, <35%, <30%, <25%, <20%, <15%, <10%, <5%, >0% (when the target O3 / P2 mixed phase sodium-doped layered oxide has the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2 is not 37% or when the target O3 / P2 mixed phase contains sodium-doped layered oxides having the formula Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 Since the amount of O3 phase plus the amount of P2 phase are normalized to equal 100%, the amount of O3 phase present can be unambiguously inferred from the amount of P2 phase (as described above).
[0154] The reaction between the precursor materials usually occurs during the heating step ii) of the method, and this usually involves heating the mixture of precursor materials at a temperature of at least 500°C, preferably at least 600°C, further preferably at least 700°C, further preferably at least 800°C, particularly preferably at least 850°C, and ideally at least 825°C, a single temperature or a temperature range. The maximum temperature is preferably 1200°C, further preferably 1150°C. As described above, when the mixture of precursor materials is selected to prepare a product having the formula Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 When the O3 / P2 mixed phase of the layered oxide material of formula Na2O2 contains sodium, the heating step does not include heating at 900°C for 10 hours, wherein the material comprises a mixture of phases in which the first phase has an O3 type structure and the second phase has a P2 type structure, and wherein the first phase and the second phase are present in a ratio of 63:37; and when the mixture of precursor materials is selected to prepare a layered oxide material having the formula Na2O2, the heating step does not include heating at 900°C for 10 hours. 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083When the O3 / P2 mixed phase of O2 contains sodium-doped layered oxide material, excluding heating at 900°C for 4 minutes, the material comprises a mixture of phases, wherein the first phase has an O3 type structure and the second phase has a P2 type structure, and wherein the first phase and the second phase are present in a ratio of 97:3.
[0155] Advantageously, the heating step ii) comprises heating the mixture of precursor materials to the desired reaction temperature for a reaction time (as described above) of 30 seconds to 64 hours, preferably 30 seconds to 44 hours, further preferably 30 seconds to 20 hours, particularly preferably 1 minute to 12 hours, most preferably greater than 4 minutes to less than 10 hours, and ideally 8 to 12 hours. It is expected that commercial-scale preparation requires a reaction time of less than 8 hours, for example less than 1 hour.
[0156] As described above, all of the above-mentioned O3 / P2 mixed phase sodium-containing doping materials according to the present invention can be prepared according to the method of the present invention.
[0157] The precursor material used in step i) of the method of the present invention may be selected from any suitable compound containing one or more of the metal elements present in the target O3 / P2 mixed phase sodium-doped layered oxide material. Preferably, the mixture of precursor materials contains one or more compounds selected from the group consisting of Na2CO3, NiCO3, NiCO3•2Ni(OH)2•xH2O, MnO2, MnO, MnCO3, Mn2O3, Mg(OH)2, TiO2, Fe2O3, CoCO3, Co3O4, Al(OH)3, CuO, CaCO3, ZnO, Cr2O3, MoO3, MoO2, V2O3, V2O5, Zr(OH)4, Al(OH)3.
[0158] Ideally, the methods of the present invention are conducted as "solid state" reactions, i.e., reactions in which all of the precursor materials (reactants) are in solid form and are substantially free of any reaction medium (e.g., solvent). However, in some cases, solution-based reactions may also be used, in which a mixture of precursor materials is formed by mixing, suspending, or dissolving one or more of the precursor materials in a solvent (e.g., water).
[0159] The mixture of precursor materials preferably comprises at least two precursor materials which contain a combined total amount of each metal atom between them equal to the stoichiometric ratio present in the target O3 / P2 mixed phase sodium-containing doped layered oxide material having the above general formula.
[0160] The precursor materials can be mixed (preferably intimately) using any known method. Further preferably, one or more of the precursor materials are in particulate form, and this can be achieved using a variety of methods, such as by finely grinding one or more of the precursor materials using, for example, a pestle and mortar or a ball mill, and then optionally using, for example, a micro-powder mill or a mixing mill to mix two or more of the precursor materials together. Alternatively, two or more precursor materials can be mixed while finely grinding. Grinding and / or mixing preferably have sufficient duration to produce finely ground and / or uniformly mixed powders. In order to assist the grinding and / or mixing process, it is found that the use of a dispersant (preferably a material that is easily removed, such as a low boiling point material, such as acetone) to assist the grinding and / or mixing process is useful, but the dispersant will preferably be at least substantially removed before the heating step. Other known techniques, such as high-energy ball milling and microwave activation, can also be used to help prepare precursor materials, such as to increase their reactivity.
[0161] Typically, the reaction is carried out at atmospheric pressure, in air or in a non-oxidizing atmosphere such as nitrogen, argon or another inert gas or mixture thereof, but may also be carried out at air or gas pressures greater than atmospheric pressure, or under vacuum.
[0162] The above method of the present invention advantageously provides a method for preparing an O3 / P2 mixed phase sodium-doped layered oxide material selected from the following:
[0163] NeNi 0.400 Mn 0.490 Mg 0.100 Ti 0.010 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0164] Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 (comprising 1% to 99%, but not 97%, of a first phase having an O3-type structure, and 99% to 1%, but not 3%, of a second phase having a P2-type structure);
[0165] Na 0.925 Ni 0.4525 Mn 0.5275 Mg 0.01 Ti 0.01 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0166] Na 0.867 Ni0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0167] Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 O2 (comprising 1% to 99%, but not 63%, of a first phase having an O3-type structure, and 99% to 1%, but not 37%, of a second phase having a P2-type structure);
[0168] Na 0.8 Ni 0.35 Mn 0.48 Mg 0.05 Ti 0.12 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0169] Na 0.77 Ni 0.28 Mn 0.31 Mg 0.05 Ti 0.25 Fe 0.11 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0170] Na 0.77 Ni 0.225 Mn 0.115 Mg 0.01 Ti 0.35 Fe 0.3 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0171] Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0172] Na 0.833 Ni 0.317 Mn 0.417 Mg 0.05 Ti 0.117 Co 0.1O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0173] Na 0.867 Ni 0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0174] Na 0.85 Ni 0.325 Mn 0.525 Mg 0.100 Ti 0.05 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0175] Na 0.85 Ni 0.325 Mn 0.499 Mg 0.100 Ti 0.076 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0176] Na 0.77 Ni 0.305 Mn 0.51 Mg 0.025 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0177] Na 0.77 Ni 0.305 Mn 0.535 Mg 0.025 Ti 0.025 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0178] NeNi 0.4 Mn 0.49 Mg 0.1 Ti 0.01 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0179] Na 0.77Ni 0.28 Mn 0.51 Mg 0.05 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0180] Na 0.833 Fe 0.200 Mn 0.483 Mg 0.0917 Cu 0.225 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0181] NaLi 0.05 Ni 0.3 Mn 0.525 Mg 0.025 Cu 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0182] Na 0.775 Ni 0.35 Mn 0.475 Ti 0.1 Al 0.075 O2 (comprising 1% to 99% of a first phase having an O3 type structure and 99% to 1% of a second phase having a P2 type structure); and
[0183] Na 0.833 Ca 0.05 Ni 0.3417 Mn 0.4417 Mg 0.125 Ti 0.0917 O2 (comprising 1% to 99% of a first phase having an O3 type structure and 99% to 1% of a second phase having a P2 type structure).
[0184] The percentage value of each of the first phase and the second phase is based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material.
[0185] The present invention also provides the use of the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention as an electrode active material, preferably as a cathode active material.
[0186] Furthermore, the present invention provides an electrode, preferably a cathode, comprising one or more O3 / P2 mixed phase sodium-doped layered oxide materials according to the present invention.
[0187] The most preferred electrode of the present invention comprises one or more O3 / P2 mixed phase sodium-doped layered oxide materials selected from the following:
[0188] NeNi 0.400 Mn 0.490 Mg 0.100 Ti 0.010 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0189] Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 (comprising 1% to 99%, but not 97%, of a first phase having an O3-type structure, and 99% to 1%, but not 3%, of a second phase having a P2-type structure);
[0190] Na 0.925 Ni 0.4525 Mn 0.5275 Mg 0.01 Ti 0.01 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0191] Na 0.867 Ni 0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0192] Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 O2 (comprising 1% to 99%, but not 63%, of a first phase having an O3-type structure, and 99% to 1%, but not 37%, of a second phase having a P2-type structure);
[0193] Na 0.8 Ni 0.35 Mn 0.48 Mg 0.05 Ti 0.12 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0194] Na 0.77 Ni 0.28 Mn0.31 Mg 0.05 Ti 0.25 Fe 0.11 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0195] Na 0.77 Ni 0.225 Mn 0.115 Mg 0.01 Ti 0.35 Fe 0.3 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0196] Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0197] Na 0.833 Ni 0.317 Mn 0.417 Mg 0.05 Ti 0.117 Co 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0198] Na 0.867 Ni 0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0199] Na 0.85 Ni 0.325 Mn 0.525 Mg 0.100 Ti 0.05 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0200] Na 0.85 Ni 0.325 Mn 0.499 Mg 0.100 Ti 0.076 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0201] Na 0.77 Ni 0.305 Mn 0.51 Mg 0.025 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0202] Na 0.77 Ni 0.305 Mn 0.535 Mg 0.025 Ti 0.025 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0203] NeNi 0.4 Mn 0.49 Mg 0.1 Ti 0.01 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0204] Na 0.77 Ni 0.28 Mn 0.51 Mg 0.05 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0205] Na 0.833 Fe 0.200 Mn 0.483 Mg 0.0917 Cu 0.225 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0206] NaLi 0.05 Ni 0.3 Mn 0.525 Mg 0.025 Cu 0.1 O2 (comprising 1% to 99% of a first phase having an O3-type structure and 99% to 1% of a second phase having a P2-type structure);
[0207] Na 0.775 Ni 0.35Mn 0.475 Ti 0.1 Al 0.075 O2 (comprising 1% to 99% of a first phase having an O3 type structure and 99% to 1% of a second phase having a P2 type structure); and
[0208] Na 0.833 Ca 0.05 Ni 0.3417 Mn 0.4417 Mg 0.125 Ti 0.0917 O2 (comprising 1% to 99% of a first phase having an O3 type structure and 99% to 1% of a second phase having a P2 type structure).
[0209] The percentage value of each of the first phase and the second phase is based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material.
[0210] The electrodes of the present invention are suitable for many different applications, including sodium ion batteries, which can be widely used in, for example, energy storage devices, such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices. Preferably, the electrodes of the present invention can be used in combination with a counter electrode and one or more electrolyte materials. The electrolyte material can be any suitable material, including conventional, known or hitherto unknown materials.
[0211] Finally, the present invention provides energy storage devices, such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices, which contain the O3 / P2 mixed phase sodium-doped layered oxide (preferably nickelate) material as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0213] The present invention will now be described with reference to the following drawings, in which:
[0214] Figure 1 It is a known material NaNi 0.5 Mn 0.5 XRD pattern of O2 (CE1);
[0215] Figure 2 Shows hard carbon / / NaNi 0.5 Mn 0.5 Cell voltage curves for the first four charge / discharge cycles of the O2 (CE1) cell (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]);
[0216] Figure 3Constant current cycling (CC / CV) of an all-Na-ion cell comprising hard carbon and O3-NaNi0.5Mn0.5O2 (CE1) in the voltage range of 1.0-4.3 V at 30 °C in an electrolyte comprising 0.5 M NaPF6 dissolved in a mixture of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC), with a glass fiber filter paper (Whatman® GF / A grade) as a separator;
[0217] Figure 4 It is a known material NaNi 0.5 Ti 0.5 XRD pattern of O2 (CE2);
[0218] Figure 5 Shows hard carbon / / NaNi 0.5 Ti 0.5 Cell voltage curves for the first four charge / discharge cycles of the O2 (CE2) cell (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]);
[0219] Figure 6 It shows that the hard carbon and O3-NaNi 0.5 Ti 0.5 Constant current cycling (CC / CV) of all-Na-ion cells for O2 (CE2) in the voltage range of 1.0-4.3 V at 30 °C in an electrolyte containing 0.5 M NaPF6 dissolved in a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) with glass fiber filter paper (Whatman® GF / A grade) as separator;
[0220] Figure 7 It is a known compound P2-Na 0.667 Ni 0.333 Mn 0.667 XRD pattern of O2 (CE3);
[0221] Figure 8 Shows hard carbon / / Na 0.667 Ni 0.333 Mn 0.667 Cell voltage curves for the first four charge / discharge cycles of the O2 (CE3) cell (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]);
[0222] Fig. 9 It shows that the hard carbon and P2-Na 0.667 Ni 0.333 Mn 0.667Constant current cycling (CC / CV) of all-Na-ion cells for O2 (CE3) in the voltage range of 1.0-4.3 V at 30 °C in an electrolyte containing 0.5 M NaPF6 dissolved in a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) with glass fiber filter paper (Whatman® GF / A grade) as separator;
[0223] Fig.10 O3 / P2-Na prepared in Example 2 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 XRD pattern of O2;
[0224] Fig.11 Shows hard carbon / / Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 O (Example 2) Cell voltage curves for the first 4 charge / discharge cycles of the cell (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]);
[0225] Fig.12 It shows that the hard carbon and O3 / P2-Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Constant current cycling (CC / CV) of an all-Na-ion cell with 100% NaOH (Example 2) in the voltage range of 1.0-4.3 V at 30 °C in an electrolyte comprising 0.5 M NaPF6 dissolved in a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC), using a glass fiber filter paper (Whatman® GF / A grade) as a separator;
[0226] Fig.13 It is the O3 / P2-Na prepared in Example 4 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 XRD pattern of O2;
[0227] Fig.14 Shows hard carbon / / Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1Cell voltage curves for the first 4 charge / discharge cycles of the O2 (Example 4) cell (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]);
[0228] Fig.15 It shows that the hard carbon and O3 / P2-Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Constant current cycling (CC / CV) of an all-Na-ion cell with 100% NaOH (Example 4) in the voltage range of 1.0-4.3 V at 30 °C in an electrolyte comprising 0.5 M NaPF6 dissolved in a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC), using a glass fiber filter paper (Whatman® GF / A grade) as a separator;
[0229] Fig.16 It is the O3 / P2-Na prepared in Example 8 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 XRD pattern of O2;
[0230] Fig.17 Shows hard carbon / / Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 Cell voltage curves for the first four charge / discharge cycles of the O2 (Example 8) cell (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]);
[0231] Fig.18 It shows that the hard carbon and O3 / P2-Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 Constant current cycling (CC / CV) of an all-Na-ion cell with 100% NaOH (Example 8) in the voltage range of 1.0-4.3 V at 30 °C in an electrolyte comprising 0.5 M NaPF6 dissolved in a mixture of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC), using a glass fiber filter paper (Whatman® GF / A grade) as a separator;
[0232] Fig.19 It is shown in the preparation of Na 0.867 Ni 0.333 Mn0.467 Mg 0.1 Ti 0.1 A graph showing the relationship between the reaction temperature and the amount of the O3-type phase relative to the amount of the P2-type phase at O2;
[0233] Fig. 20 It is shown in the preparation of Na 0.8 Ni 0.35 Mn 0.48 Mg 0.05 Ti 0.12 a graph of the relationship between the reaction temperature and the amount of O3-type phase relative to the amount of P2-type phase at O2; and
[0234] Fig.21 It is shown in the preparation of Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 A graph showing the relationship between the reaction temperature and the amount of O3-type phase relative to the amount of P2-type phase at O2.
[0235] Details
[0236] General method for making the O3 / P2 mixed phase sodium-doped layered oxide material of the present invention:
[0237] 1) mixing precursor materials together to provide a stoichiometric ratio of metal atoms present in the target O3 / P2 mixed phase sodium-doped layered oxide material of the above general formula, and pressing the resulting precursor mixture into pellets;
[0238] 2) heating the resulting particulate precursor mixture in a furnace under a suitable atmosphere including, for example, ambient air, nitrogen, or an inert atmosphere (e.g., argon) (the gas may flow but need not, and may be pure or a mixture) over a ramp time of 0 to 20 hours until the particulate mixture reaches the desired reaction temperature (which will be a temperature of at least 500°C). The ramp rate used will be the heating rate (°C / min) required to ensure uniform heating of the reactants to the required reaction temperature in a reasonable time. Those skilled in the art will appreciate that this will depend on the efficiency of the heating equipment used, whether a continuous feed furnace / kiln is used, whether the equipment and / or reactants are preheated, and the batch size. Typical ramp rates are 2°C to 20°C per minute. Heating is continued for a reaction time of 30 seconds to a maximum of 64 hours until the target O3 / P2 mixed phase sodium-doped layered oxide material is formed; and
[0239] 3) Cooling and optionally grinding the target material into powder.
[0240] Table 1 below lists the precursor materials and heating conditions used to prepare O3 / P2 mixed phase sodium-doped layered oxide materials.
[0241] Table 1
[0242]
[0243]
[0244]
[0245]
[0246]
[0247] Product analysis using XRD
[0248] Analysis is performed by X-ray diffraction techniques using a Siemens® D5000 powder diffractometer to confirm that the desired target composition has been produced, to determine the phase purity of the product material, and to identify the types of impurities present. From this information, the lattice parameters of the unit cell and the relative phase ratio can be determined.
[0249] The general XRD operating conditions used to analyze the materials are as follows:
[0250] Slit size: 1 mm, 1 mm, 0.1 mm
[0251] Range: 2θ = 5° - 60°
[0252] X-ray wavelength = 1.5418 Å (Cu Kα)
[0253] Speed: 1.0 sec / step
[0254] Increment: 0.025°
[0255] Electrochemical results
[0256] The target composition is tested using a Na-ion test cell employing a hard carbon anode. The cell can be prepared using the following process:
[0257] The Na ion electrochemical test cell containing the active materials was constructed as follows:
[0258] General process for preparing hard carbon Na-ion batteries
[0259] The positive electrode was prepared by solvent casting a slurry of active material, conductive carbon, binder and solvent. The conductive carbon used was Super C65C65 (Timcal®). PVdF was used as a binder and N-methyl-2-pyrrolidone (NMP) was used as a solvent. The slurry was then cast onto aluminum foil and heated until most of the solvent evaporated and an electrode film was formed. The electrode was then dried at about 120°C under dynamic vacuum. The electrode film contained the following components expressed in weight percentage: 89% active material (doped layered oxide composition), 6% Super C65 carbon and 5% PVdF binder.
[0260] The negative electrode was prepared by solvent casting a slurry of hard carbon active material (Carbotron® P / J, supplied by Kureha), conductive carbon, binder and solvent. The conductive carbon used was Super C65 (Timcal®). PVdF was used as a binder and N-methyl-2-pyrrolidone (NMP) was used as a solvent. The slurry was then cast onto aluminum foil and heated until most of the solvent evaporated and an electrode film was formed. The electrode was then further dried at about 120°C under dynamic vacuum. The electrode film contained the following components expressed in weight percentage: 88% active material, 3% Super C65 carbon and 9% PVdF binder.
[0261] Battery Test
[0262] Using a constant current cycling technique, the batteries were tested as follows.
[0263] The battery was cycled at a given current density between preset voltage limits. A commercial battery cycler from Maccor Inc. (Tulsa, OK, USA) was used. During charging, alkali ions are released from the cathode active material. During discharge, alkali ions are reinserted into the cathode active material.
[0264] A summary of the test results is given in Table 2 below:
[0265] Table 2
[0266]
[0267]
[0268]
[0269] Results and Discussion
[0270] Comparative Example 1
[0271] NeNi 0.5 Mn 0.5 O2 (sample X2895)
[0272] Figure 1 Shows the known material NaNi 0.5 Mn 0.5 X-ray diffraction pattern of O2 (sample number X2895). The pattern shows that the material conforms to the single-phase doped layered O3 structure.
[0273] Figure 2 and Figure 3 The data shown in the figure are from the Na-ion battery (cell number 803039) in O3-NaNi 0.5 Mn 0.5 Constant current cycling data for an O2 cathode active material coupled to a hard carbon anode material. The electrolyte used was a solution of 0.5 M NaPF6 in a mixture of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC). The current was approximately 0.25 mA / cm2 between voltage limits of 1.00 to 4.3 V. 2 The constant current data were collected at a current density of . To ensure that the Na-ion battery was fully charged, the battery was kept at a constant potential of 4.3 V at the end of the constant current charging process until the current density dropped to 10% of the constant current value. The tests were performed at 30 °C. During the charging process, the sodium ions were dissociated from the cathode active material and embedded in the hard carbon anode. During the subsequent discharge process, the sodium ions were dissociated from the hard carbon and then re-intercalated into the cathode active material.
[0274] Figure 2 Shows hard carbon / / NaNi 0.5 Mn 0.5 Cell voltage curves (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]) for the first four charge / discharge cycles of the O2 cell. These data show relatively poor capacity retention and relatively high voltage hysteresis (i.e., voltage difference between charge and discharge processes), indicating relatively poor kinetic reversibility of the Na-ion deintercalation reaction in this cathode material.
[0275] Figure 3 Shows hard carbon / / NaNi 0.5 Mn 0.5 Constant current cycle life curve of O2 battery, i.e. the relationship between cathode discharge specific capacity [mAh / g] and cycle number. For cycle 1, the cathode discharge specific capacity is about 141 mAh / g. For cycle 9, the cathode discharge specific capacity is about 101 mAh / g. This represents a capacity decay of 28.37% over 9 cycles, or an average of 3.15% per cycle. The cathode materials tested clearly show relatively poor capacity retention performance.
[0276] Comparative Example 2
[0277] NeNi 0.5 Ti 0.5 O2 (sample) X2896
[0278] Figure 4 The XRD pattern shown confirms that the material conforms to the single-phase doped layered O3 type structure.
[0279] Figure 5 and Figure 6 The data shown in the figure are from the Na-ion battery (battery number 803040RH) in O3-NaNi 0.5 Ti 0.5 Constant current cycling data for an O2 cathode active material coupled to a hard carbon anode material. The electrolyte used was a solution of 0.5 M NaPF6 in a mixture of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC). The current was approximately 0.25 mA / cm2 between voltage limits of 1.00 to 4.3 V. 2 To ensure that the Na-ion battery is fully charged, the battery was kept at a constant potential of 4.3 V at the end of the constant current charging process until the current density dropped to 10% of the constant current value. The test was performed at 30 °C.
[0280] During the charging process, sodium ions are released from the cathode active material and embedded in the hard carbon anode. During the subsequent discharge process, sodium ions are released from the hard carbon and then re-intercalated into the cathode active material. Figure 5 Shows hard carbon / / NaNi 0.5 Ti 0.5 Cell voltage curves (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]) for the first four charge / discharge cycles of the O2 cell. These data show relatively poor capacity retention and relatively high voltage hysteresis (i.e., voltage difference between charge and discharge processes), indicating relatively poor kinetic reversibility of the Na-ion deintercalation reaction in this cathode material.
[0281] Figure 6 Shows hard carbon / / NaNi 0.5 Ti 0.5 Constant current cycle life curve of O2 battery, i.e., the relationship between cathode discharge specific capacity [mAh / g] and cycle number. For cycle 1, the cathode discharge specific capacity is about 107 mAh / g. For cycle 19, the cathode discharge specific capacity is about 53 mAh / g. This represents a capacity decay of 50.47% over 19 cycles, or an average of 2.66% per cycle. The cathode materials tested clearly show relatively poor capacity retention performance.
[0282] Comparative Example 3
[0283] Na 0.667 Ni 0.333 Mn 0.667 O2 (sample X2748)
[0284] Figure 7 Shows the known material Na 0.667 Ni 0.333 Mn 0.667 X-ray diffraction pattern of O2 (sample number X2748). The pattern shows that the material conforms to the layered P2 type structure.
[0285] Figure 8 and Fig. 9 The data shown in the figure are from the P2-Na 0.667 Ni 0.333 Mn 0.667 Constant current cycling data for an O2 cathode active material coupled to a hard carbon anode material. The electrolyte used was a solution of 0.5 M NaPF6 in a mixture of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC). The current was approximately 0.25 mA / cm2 between voltage limits of 1.00 to 4.3 V. 2 To ensure that the Na-ion battery is fully charged, the battery is kept at a constant potential of 4.3 V at the end of the constant current charging process until the current density drops to 10% of the constant current value. The test is performed at 30 °C.
[0286] During the charging process, sodium ions are released from the cathode active material and embedded in the hard carbon anode. During the subsequent discharge process, sodium ions are released from the hard carbon and then re-intercalated into the cathode active material. Figure 8 Shows hard carbon / / Na 0.667 Ni 0.333 Mn 0.667 Cell voltage curves (i.e., Na-ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]) for the first four charge / discharge cycles of the O2 cell. These data show relatively poor capacity retention and relatively high voltage hysteresis (i.e., voltage difference between charge and discharge processes), indicating relatively poor kinetic reversibility of the Na-ion deintercalation reaction in this cathode material.
[0287] Fig. 9 Shows hard carbon / / Na 0.667 Ni 0.333 Mn 0.667Constant current cycle life curve of O2 battery, i.e. the relationship between cathode discharge specific capacity [mAh / g] and cycle number. For cycle 1, the cathode discharge specific capacity is about 127 mAh / g. For cycle 38, the cathode discharge specific capacity is about 62 mAh / g. This represents a capacity decay of 51.18% over 38 cycles, or an average of 1.35% per cycle. The cathode materials tested clearly show relatively poor capacity retention performance.
[0288] A series of results according to representative embodiments of the present invention
[0289] Example 2
[0290] Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 O2 (sample X2505)
[0291] Fig.10 Shows the material Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 X-ray diffraction pattern of O2 (sample number X2505). The pattern shows that the material contains a mixture of phases of a first phase having an O3-type structure and a second phase having a P2-type structure. The percentage of the amount of the first and second phases was determined using Rietveld refinement.
[0292] Fig.11 and 12 The data shown in the figure are from the O3 / P2-Na in a Na-ion battery (cell number 608010). 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Constant current cycling data for an O2 cathode active material coupled to a hard carbon anode material. The electrolyte used was a solution of 0.5 M NaPF6 in a mixture of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC). The current was approximately 0.25 mA / cm2 between voltage limits of 1.00 to 4.3 V. 2 To ensure that the Na-ion battery is fully charged, the battery is kept at a constant potential of 4.3 V at the end of the constant current charging process until the current density drops to 10% of the constant current value. The test is performed at 30 °C.
[0293] During the charging process, sodium ions are released from the cathode active material and embedded in the hard carbon anode. During the subsequent discharge process, sodium ions are released from the hard carbon and then re-intercalated into the cathode active material. Fig.11 Shows hard carbon / / Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Cell voltage curves (i.e., Na ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]) for the first four charge / discharge cycles of the O2 cell. These data demonstrate excellent capacity retention and low voltage hysteresis (i.e., voltage difference between charge and discharge processes), indicating excellent kinetic reversibility of the Na ion deintercalation reaction. In addition, the roughly symmetrical nature of the charge / discharge voltage curves confirms the excellent reversibility of the deintercalation reaction.
[0294] Fig.12 Shows hard carbon / / Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Constant current cycle life curve of O2 battery, i.e. the relationship between cathode discharge specific capacity [mAh / g] and cycle number. For cycle 1, the cathode discharge specific capacity is about 144 mAh / g. For cycle 36, the cathode discharge specific capacity is about 142 mAh / g. This represents a capacity decay of 1.39% over 36 cycles, or an average of 0.04% per cycle. The cathode materials tested clearly show excellent capacity retention performance.
[0295] Example 4
[0296] Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 O2 (sample X2506)
[0297] Fig.13 Shows the material Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 X-ray diffraction pattern of O2 (sample number X2506). The pattern shows that the material contains a mixture of phases of a first phase having an O3-type structure and a second phase having a P2-type structure. The percentage of the amount of the first and second phases was determined using Rietveld refinement.
[0298] Fig.14 and 15The data shown in the figure are from the O3 / P2-Na in a Na-ion battery (cell number 608011). 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Constant current cycling data for an O2 cathode active material coupled to a hard carbon anode material. The electrolyte used was a solution of 0.5 M NaPF6 in a mixture of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC). The current was approximately 0.25 mA / cm2 between voltage limits of 1.00 to 4.3 V. 2 To ensure that the Na-ion battery is fully charged, the battery is kept at a constant potential of 4.3 V at the end of the constant current charging process until the current density drops to 10% of the constant current value. The test is performed at 30 °C.
[0299] During the charging process, sodium ions are released from the cathode active material and embedded in the hard carbon anode. During the subsequent discharge process, sodium ions are released from the hard carbon and then re-intercalated into the cathode active material. Fig.14 Shows hard carbon / / Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Cell voltage curves (i.e., Na ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]) for the first four charge / discharge cycles of the O2 cell. These data demonstrate excellent capacity retention and low voltage hysteresis (i.e., voltage difference between charge and discharge processes), indicating excellent kinetic reversibility of the Na ion deintercalation reaction. In addition, the roughly symmetrical nature of the charge / discharge voltage curves confirms the excellent reversibility of the deintercalation reaction.
[0300] Fig.15 Shows hard carbon / / Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 Constant current cycle life curve of O2 battery, i.e. the relationship between cathode discharge specific capacity [mAh / g] and cycle number. For cycle 1, the cathode discharge specific capacity is about 143mAh / g. For cycle 30, the cathode discharge specific capacity is about 140 mAh / g. This represents a capacity decay of 2.10% over 30 cycles, or an average of 0.07% per cycle. The cathode materials tested clearly show excellent capacity retention performance.
[0301] Example 8
[0302] Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 O2 (sample X2663)
[0303] Fig.16 Shows the material Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 X-ray diffraction pattern of O2 (sample number X2663). The pattern shows that the material contains a mixture of phases of a first phase having an O3-type structure and a second phase having a P2-type structure. From these structural data, the percentages of the amounts of the first and second phases are determined.
[0304] Fig.17 and 18 The data shown in the figure are from the O3 / P2-Na in a Na-ion battery (cell number 706006). 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 Constant current cycling data for an O2 cathode active material coupled to a hard carbon anode material. The electrolyte used was a solution of 0.5 M NaPF6 in a mixture of ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC). The current was approximately 0.25 mA / cm2 between voltage limits of 1.00 to 4.3 V. 2 To ensure that the Na-ion battery is fully charged, the battery is kept at a constant potential of 4.3 V at the end of the constant current charging process until the current density drops to 10% of the constant current value. The test is performed at 30 °C.
[0305] During the charging process, sodium ions are released from the cathode active material and embedded in the hard carbon anode. During the subsequent discharge process, sodium ions are released from the hard carbon and then re-intercalated into the cathode active material. Fig.17 Shows hard carbon / / Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117Cell voltage curves (i.e., Na ion cell voltage [V] versus cumulative cathode specific capacity [mAh / g]) for the first four charge / discharge cycles of the O2 cell. These data demonstrate excellent capacity retention and low voltage hysteresis (i.e., voltage difference between charge and discharge processes), indicating excellent kinetic reversibility of the Na ion deintercalation reaction. In addition, the roughly symmetrical nature of the charge / discharge voltage curves confirms the excellent reversibility of the deintercalation reaction.
[0306] Fig.18 Shows hard carbon / / Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 Constant current cycle life curve of O2 battery, i.e. the relationship between cathode discharge specific capacity [mAh / g] and cycle number. For cycle 1, the cathode discharge specific capacity is about 132 mAh / g. For cycle 32, the cathode discharge specific capacity is about 129 mAh / g. This represents a capacity decay of 2.27% over 32 cycles, or an average of 0.07% per cycle. The cathode materials tested clearly show excellent capacity retention performance.
[0307] Relationship between reaction temperature and the amount of O3 phase prepared relative to the amount of P2 phase prepared
[0308] Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 O2
[0309] Table 3
[0310]
[0311] Table 3 and Fig.19 It is shown that as the synthesis temperature increases, the proportion of the phase with the O3 structure increases relative to the proportion of the phase with the P2 structure.
[0312] Na 0.8 Ni 0.35 Mn 0.48 Mg 0.05 Ti 0.12 O2
[0313] Table 4
[0314]
[0315] Table 4 and Fig. 20 It is shown that as the synthesis temperature increases, the proportion of the phase with the O3 structure increases relative to the proportion of the phase with the P2 structure.
[0316] Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 O2
[0317] Table 5
[0318]
[0319] Table 5 and Fig.21 It is shown that as the synthesis temperature increases, the proportion of the phase with the O3 structure increases relative to the proportion of the phase with the P2 structure.
Claims
1. A method for preparing an O3 / P2 mixed phase sodium-doped layered oxide material, wherein the O3 / P2 mixed phase sodium-doped layered oxide material comprises a mixture of phases, wherein the first phase has one or more O3 type structures and the second phase has one or more P2 type structures; and wherein the O3 / P2 mixed phase sodium-doped layered oxide material has the following general formula: And a A b I 1 c I 2 d I 3 e I 4 f I 5 g Oh 2±δ ; in: A is at least one alkali metal selected from lithium and potassium; M 1 It is nickel with an average oxidation state of 2+; M 2 It is manganese with an average oxidation state of 4+; M 3 is one or more metals selected from magnesium, calcium, copper, zinc and cobalt having an average oxidation state of 2+; M 4 is one or more metals selected from manganese, titanium and zirconium having an average oxidation state of 4+; and M 5 is one or more metals selected from aluminum, iron, cobalt, molybdenum, chromium, vanadium, scandium and yttrium having an average oxidation state of 3+; in: a>0; 0 ≤ b < 0.5; a>b; 0.75 < (a+b) ≤ 1.0; 0 < c < 0.5; d ﹥ 0; f ≥ 0; e > 0; 0 ≤ g < 0.5; 0 ≤ δ ≤ 0.1; Where: a, b, c, d, e, f, and g are chosen to maintain electrical neutrality; Wherein, based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the O3 / P2 mixed phase sodium-doped layered oxide material comprises >60 to 99% of the first phase, and <40 to 1% of the second phase, and the method comprises the following steps: i) forming a mixture of precursor materials to provide a stoichiometric ratio of metal atoms present in an O3 / P2 mixed phase sodium-doped layered oxide material of the general formula; and ii) gradually heating the resulting mixture of precursor materials to a temperature of at least 500° C. at a heating rate of 2° C. to 20° C. per minute until a first phase ratio between the P2 phase and the O3 phase is achieved; and iii) maintaining said temperature for a reaction time of 30 seconds to 64 hours until a second phase ratio between the P2 phase and the O3 phase is achieved; and iv) cooling to produce the O3 / P2 mixed phase sodium-doped layered oxide material; The method described does not involve any of the following: i) Formation provides a presence of Na 0.833 Ni 0.317 Mn 0.467 Mg 0.100 Ti 0.117 A mixture of precursor materials of an O3 / P2 mixed phase containing sodium doped layered oxide materials in a stoichiometric ratio of metal atoms; and ii) heating the resulting mixture at 900° C. for 10 hours to produce an O3 / P2 mixed phase sodium-doped layered oxide material, the material comprising a mixture of phases in which a first phase has an O3 type structure and a second phase has a P2 type structure, wherein an amount of the first phase is 63% and an amount of the second phase is 37% based on the combined total moles of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material; or i) Formation provides a presence of Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 A mixture of precursor materials of an O3 / P2 mixed phase containing sodium doped layered oxide materials in a stoichiometric ratio of metal atoms; and ii) heating the resulting mixture at 900° C. for 4 minutes to produce an O3 / P2 mixed phase sodium-doped layered oxide material, the material comprising a mixture of phases in which a first phase has an O3 type structure and a second phase has a P2 type structure, wherein an amount of the first phase is 97% and an amount of the second phase is 3% based on the combined total moles of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material.
2. The method according to claim 1, which is used to prepare an O3:P2 mixed phase sodium-doped layered oxide material selected from the group consisting of: NeNi 0.400 Mn 0.490 Mg 0.100 Ti 0.010 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.95 Ni 0.3167 Mn 0.3167 Mg 0.1583 Ti 0.2083 O2 (comprising >60% to 99%, but not 97%, of a first phase having an O3-type structure and <40% to 1%, but not 3%, of a second phase having a P2-type structure); Na 0.925 Ni 0.4525 Mn 0.5275 Mg 0.01 Ti 0.01 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.867 Ni 0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.833 Ni 0.317 Mn 0.467 Mg 0.1 Ti 0.117 O2 (comprising >60% to 99%, but not 63%, of a first phase having an O3-type structure and <40% to 1%, but not 37%, of a second phase having a P2-type structure); Na 0.8 Ni 0.35 Mn 0.48 Mg 0.05 Ti 0.12 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.77 Ni 0.28 Mn 0.31 Mg 0.05 Ti 0.25 Fe 0.11 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.77 Ni 0.225 Mn 0.115 Mg 0.01 Ti 0.35 Fe 0.3 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.867 Ni 0.333 Mn 0.467 Mg 0.1 Ti 0.1 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.833 Ni 0.317 Mn 0.417 Mg 0.05 Ti 0.117 Co 0.1 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.867 Ni 0.383 Mn 0.467 Mg 0.05 Ti 0.1 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.85 Ni 0.325 Mn 0.525 Mg 0.100 Ti 0.05 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.85 Ni 0.325 Mn 0.499 Mg 0.100 Ti 0.076 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.77 Ni 0.305 Mn 0.51 Mg 0.025 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.77 Ni 0.305 Mn 0.535 Mg 0.025 Ti 0.025 Al 0.055 Co 0.055 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); NeNi 0.4 Mn 0.49 Mg 0.1 Ti 0.01 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.77 Ni 0.28 Mn 0.51 Mg 0.05 Ti 0.05 Al 0.055 Co 0.055 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); Na 0.775 Ni 0.35 Mn 0.475 Ti 0.1 Al 0.075 O2 (comprising >60% to 99% of a first phase having an O3-type structure and <40% to 1% of a second phase having a P2-type structure); and Na 0.833 Ca 0.05 Ni 0.3417 Mn 0.4417 Mg 0.125 Ti 0.0917 O2 (comprising >60% to 99% of a first phase with an O3-type structure and <40% to 1% of a second phase with a P2-type structure); The percentage value of each of the first phase and the second phase is based on the total molar number of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material.
3. The method according to claim 1, wherein Step iii) involves a reaction time of 1 minute to 12 hours.
4. The method according to claim 1, wherein Step iii) comprises a reaction time of greater than 4 minutes to less than 10 hours.
5. The method according to claim 1, wherein: Step ii) comprises a reaction temperature of 700°C to 1200°C.
6. An O3 / P2 mixed phase sodium-doped layered oxide material prepared according to the method of any one of claims 1 to 5.
7. An energy storage device comprising one or more O3 / P2 mixed phase sodium-doped layered oxide materials prepared by the method according to any one of claims 1 to 5.
8. An energy storage device according to claim 7, selected from the group consisting of a battery, a rechargeable battery, an electrochemical device and an electrochromic device.
9. An electrode comprising one or more O3 / P2 mixed phase sodium-doped layered oxide materials prepared by the method according to any one of claims 1 to 5.
10. A method for adjusting the relative proportions of the O3 / P2 phases of an O3 / P2 mixed phase sodium-doped layered oxide material, wherein the O3 / P2 mixed phase sodium-doped layered oxide material comprises a mixture of phases, wherein a first phase has one or more O3 type structures and a second phase has one or more P2 type structures; and wherein the O3 / P2 mixed phase sodium-doped layered oxide material has the following general formula: And a A b I 1 c I 2 d I 3 e I 4 f I 5 g Oh 2±δ ; in: A is at least one alkali metal selected from lithium and potassium; M 1 It is nickel with an average oxidation state of 2+; M 2 It is manganese with an average oxidation state of 4+; M 3 is one or more metals selected from magnesium, calcium, copper, zinc and cobalt having an average oxidation state of 2+; M 4 is one or more metals selected from manganese, titanium and zirconium having an average oxidation state of 4+; and M 5 is one or more metals selected from aluminum, iron, cobalt, molybdenum, chromium, vanadium, scandium and yttrium having an average oxidation state of 3+; in: a>0; 0 ≤ b < 0.5; a>b; 0.75 < (a+b) ≤ 1.0; 0 < c < 0.5; d ﹥ 0; f ≥ 0; e > 0; 0 ≤ g < 0.5; 0 ≤ δ ≤ 0.1; Where: a, b, c, d, e, f, and g are chosen to maintain electrical neutrality; wherein based on the total molar amount of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the O3 / P2 mixed phase sodium-doped layered oxide material comprises >60 to 99% of the first phase, and <40 to 1% of the second phase, The method comprises: i) forming a mixture of precursor materials to provide a stoichiometric ratio of metal atoms present in an O3 / P2 mixed phase sodium-doped layered oxide material of the general formula; and ii) adjusting the ratio of the phase having an O3 structure to the phase having a P2 structure in the O3 / P2 mixed phase sodium-doped layered oxide material to be prepared by controlling the temperature of heating the mixture of the obtained precursor materials; Wherein, the temperature in step ii) is 500°C to 1200°C.
11. The method according to claim 10, wherein: The ratio of the phase having an O3 structure relative to the phase having a P2 structure is increased by increasing the reaction temperature.
12. A method for adjusting the relative proportions of the O3 / P2 phases of an O3 / P2 mixed phase sodium-doped layered oxide material, wherein the O3 / P2 mixed phase sodium-doped layered oxide material comprises a mixture of phases, wherein a first phase has one or more O3 type structures and a second phase has one or more P2 type structures; and wherein the O3 / P2 mixed phase sodium-doped layered oxide material has the following general formula: And a A b I 1 c I 2 d I 3 e I 4 f I 5 g Oh 2±δ ; in: A is at least one alkali metal selected from lithium and potassium; M 1 It is nickel with an average oxidation state of 2+; M 2 It is manganese with an average oxidation state of 4+; M 3 is one or more metals selected from magnesium, calcium, copper, zinc and cobalt having an average oxidation state of 2+; M 4 is one or more metals selected from manganese, titanium and zirconium having an average oxidation state of 4+; and M 5 is one or more metals selected from aluminum, iron, cobalt, molybdenum, chromium, vanadium, scandium and yttrium having an average oxidation state of 3+; in: a>0; 0 ≤ b < 0.5; a>b; 0.75 < (a+b) ≤ 1.0; 0 < c < 0.5; d ﹥ 0; f ≥ 0; e > 0; 0 ≤ g < 0.5; 0 ≤ δ ≤ 0.1; Where: a, b, c, d, e, f, and g are chosen to maintain electrical neutrality; wherein based on the total molar amount of the first phase and the second phase present in the O3 / P2 mixed phase sodium-doped layered oxide material, the O3 / P2 mixed phase sodium-doped layered oxide material comprises >60 to 99% of the first phase, and <40 to 1% of the second phase, The method comprises: i) forming a mixture of precursor materials to provide a stoichiometric ratio of metal atoms present in an O3 / P2 mixed phase sodium-doped layered oxide material of the general formula; and ii) adjusting the ratio of the phase having an O3 structure to the phase having a P2 structure in the O3 / P2 mixed phase sodium-doped layered oxide material to be prepared by controlling the duration of heating the resulting mixture of precursor materials; and Wherein, the duration in step ii) is 30 seconds to 64 hours.
13. The method according to claim 12, wherein: The proportion of the phase having the O3 structure relative to the phase having the P2 structure is increased by increasing the duration of heating the resulting mixture of precursor materials.